Inversion Motion of Xanthene and Detection of Its Oxidation Product Xanthone from Gas-Phase Rotational Spectroscopy - Celina Bermúdez; Manuel Goubet; Elias M. Neeman (Molecules, 2025)
The rotational spectra of xanthene and its oxidation product xanthone were investigated by combining quantum chemical calculations with Fourier transform microwave spectroscopy in a jet-cooled environment. Xanthone was unexpectedly generated in the experiment when water was present in the reservoir of xanthene leading to the total disappearance of xanthene after few hours. Structurally, xanthone shows a near planar disposition, whereas xanthene exhibits a non-planar geometry with both benzene rings twisted out of the molecular plane. This geometry enables an inversion motion between two equivalent conformers, giving rise to a splitting in the ground vibrational state. A two-state analysis of the vibration–rotation interaction for the <semantics>v=0</semantics> and <semantics>v=1</semantics> states gives an energy separation between these states (inversion splitting) of <semantics>ΔE01=4689.7095(10)<mspace width="4pt"></mspace>MHz</semantics>. This large-amplitude motion leads to vibration–rotation coupling of energy levels. A symmetric double-minimum inversion potential function was determined, resulting in a barrier of about 45 cm−1 in good agreement with that obtained by DFT quantum chemical calculations.